Activation of LC3 binders by C-S-H nucleation seeding with a new tailored admixture for low-carbon cements. - Cuesta-García, Ana María; Morales-Cantero, Alejandro; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel; Manzanec, Oliver; Dalla-Libera, Alessandro; Dhers, Sebastien; Schwesig, Peter; Borralleras, Pere; García-Aranda, Miguel Ángel (My University, 2023)
The use of supplementary cementitious materials is currently the most favorable strategy for reducing CO2 emissions in cements. Limestone Calcined Clay Cements, LC3, are a type of cement that allows the reduction of CO2 emissions up to 40%. The proportions of the mixtures can vary, but the most investigated combination, LC3-50, contains about 50 wt% clinker, 30 wt% calcined kaolinitic clay, 15 wt% limestone and an optimised calcium sulphate content. However, the mechanical strengths of LC3 at early ages are not good enough and they should be improved. One way of doing this is by employing commercial strength-enhancing (accelerator) admixtures based on C-S-H nucleation seeding. For this work, LC3-50 cements were prepared with clays with varying kaolinite contents. Mortars and pastes were fabricated using a new PCE-based superplasticizer developed to avoid the loss of fluidity at early ages typical of LC3 binders. The selected accelerator for this study was Master X-Seed STE53. The results show that the loss of fluidity of LC3 mortars during the first hours could be solved by a recently developed PCE-based superplasticizer. The compressive strengths at 1 day for LC3 mortars strikingly improved by using the C-S-H seeding admixture and this behavior was maintained for up to 28 days.
Keywords: Cemento; Calcined kaolinitic clay; C-S-H nucleation seeding; CO2 footprint; Admixtures; Superplasticizer